Screening for Dementia in Family Practice - Weston, W. Wayne (1987)
The Mini Mental State Examination (MMSE) was performed on 90% of patients over age 65 in a full-time teaching practice associated with the University of Western Ontario during a six-month study period. Before screening, dementia was documented clinically in 5.6% of the patients over age 65. The “iceberg phenomenon” did not occur: all patients with dementia identified by the MMSE had already been recognized by the physician; no new treatable problems were discovered. This study challenges the value of screening with this instrument, since it failed to identify one of the six patients in this practice with clinical dementia.